Preparing for opening night: temporal boundary objects in textually-mediated professional practice - Elisabeth Davies; Pamela J. McKenzie (Information Research: An International Electronic Journal)
The authors report on two projects in which the role of documents as temporal boundary objects mediating information practices across multiple timelines was explored. It has been suggested that studying workplace documents will uncover the information practices of professionals beyond traditional information needs and uses studies. Two workplaces were studied: a professional theatre production and a midwifery clinic. Both settings are communities constructed partly through textual dynamics and both have a pre-production phase leading to an opening night. In the theatre setting, qualitative interviews with the cast and crew and document analysis of the prompt book were the means of data collection. The midwifery clinic setting was investigated by means of interviews and follow-ups with sixteen midwife-client pairs and document analysis of the antenatal record. Preliminary thematic analysis pertaining to time and information was conducted on interview transcripts and the relevant documents. It was possible to show several instances of both the prompt book and the antenatal record being treated as a timeline by the various professionals using them. The authors conclude with a discussion of the temporal aspects of professionals' information practices as revealed by these two projects and encourage further document-focused research.